Microwave-assisted and thermal synthesis of calix[4]arene derivatives - Al-Douh, Mohammed Hadi; Ali, Yousaf; Abd Hamid, Shafida (Pleiades Publishing, 2020)
Some tert-butylcalix[4]arene derivatives were synthesized by thermal and microwave methods. The microwave method was conducted in two ways: (1) all the reactants were added in one batch and (2) the reactants were added in two batches under different conditions. Tetrabutylammonium iodide (TBAI) was used in both methods, and its effect on the reaction rate was studied. In general, the duration of the microwaveassisted reactions in the presence of TBAI, especially in the two-batch method, was shorter, and the yields were higher, than in the thermal reaction. The highest yield of (S)-glycidyl calixarene derivative by the thermal method was obtained by using K2CO3 as a base with MeCN as a solvent in the presence of TBAI, while the lowest yield of the same compound was observed when using acetone in the absence of TBAI. All the synthesized calix[4]arene derivatives were characterized by 1H and 13C NMR experiments.